Capturing the Intellectual and Literary Claims for “Name, Land and Difference” in Pronouncements of the Algerian Ulema Association and Selected Works by Mouloud Feraoun and Assia Djebar - BOUDERSA, Hemza (Journal of Human Sciences, 2022)
The initial aspiration of this research is to answer the question about which philosophy was behind picturing life in some ‘forgotten hills’ in the Algerian great Kabylia portrayed by Feraoun and Assia Djebar in their novels. Research findings affirm that the Poor Man’s Son proves to be a semi-fictional story with underlying philosophical insights; the same for ‘Fantasia, an Algerian Cavalcade’ by Assia Djebar. To a large extent, the text of Mouloud Feraoun is not ‘reportage’ as some analysts considered. Assia Djebar’s critics found philosophy behind her works; only to some extent those works echo straightforward description, but with tight connection to a profound philosophy. When it comes to this philosophy, these two novels can be unfairly considered superficial. The paper’s conclusion emphasizes the disease which resulting from colonialism which is alienation that must be cured with ‘Pen’ and ‘Mind’ revolutions that would inevitably meet the destiny which is the ‘claim for ‘freedom’ and different ‘land and name’.